Cerebral venous sinus thrombosis after COVID-19 vaccination and congenital deficiency of coagulation factors: Is there a correlation? - Federica Mele; Silvio Tafuri; Pasquale Stefanizzi; Antonio D Amati; Mariagrazia Calvano; Mirko Leonardelli; Enrica Macorano; Stefano Duma; Giovanni De Gabriele; Francesco Introna; Antonio De Donno (Human Vaccines & Immunotherapeutics, 2022)
In January 2020, SARS-COV-2 infection spread worldwide and was declared “pandemic” by WHO. Because of the high contagiousness of the virus and devastating effects of the epidemic on public health, numerous efforts have been made to develop suitable vaccines to prevent the infection. Among the side effects developed by patients who undergone vaccination, there are common symptoms but also more serious reactions such as the thrombosis syndromes. This paper presents two cases of thrombosis temporally associated with live-vectored Covid vaccination similar to vaccine-induced thrombocytopenia (VITT) in patients with inherited thrombophilia (respectively, the deficiency of protein S and a Factor II mutation). The clinical manifestation caused by VITT is characterized by widespread thrombosis especially affecting intracranial venous sinus, which may cause massive bleeding and intracranial hemorrhage. Although this condition is widely described in literature, there is no evident correlation between this side effect and inherited condition of thrombophilia. The authors suggest that the presence of inherited thrombophilia should be better investigated and, if necessary, screened during the anamnestic data collection before the vaccine administration, leading the healthcare professional to choose the appropriate vaccine to the patient.